Evaluating the Effectiveness of E-Catalog Utilization in Improving Procurement Quality Through Accessibility, Deviation Control, and Transparency - Setiawan Edi; Amirul Mustofa; Ulul Albab (Lembaga Pengembangan Kinerja Dosen, 2025)
Technological innovations have brought significant changes in the management of public administration, including the procurement of goods and services. E-Catalog is one of the innovations implemented to improve efficiency, transparency, and accessibility in the procurement process. This study aims to analyze the effectiveness of the use of E-Catalog in the city of Surabaya based on five main criteria: effort, cost-efficiency, result, cost-effectiveness, and impact. The results of the study show that E-Catalog is able to speed up the procurement process of goods and services by providing direct access to the information needed by users, without going through a time-consuming manual tender process. The system also cuts operational and administrative costs, such as printed documents and formal meetings, providing budget efficiency of up to 10% per year. In addition, user satisfaction levels increased with more than 85% of respondents feeling helped by this system. E-Catalogs not only save time and costs, but also increase transparency and accountability in procurement. All transactions are digitally documented, making the audit process easier and preventing potential irregularities. This implementation also encourages the empowerment of local MSMEs by providing easier access to government markets. Another positive impact is the increase in public trust in the government, which is supported by a transparent and inclusive system. Nonetheless, challenges such as limited technology infrastructure and intensive training need still need to be addressed to ensure the sustainability of these systems. With the integration of blockchain technology and strengthening regulations, E-Katalog has the potential to become an effective and efficient model for the procurement of goods and services, not only in Indonesia, but also at the global level. This research offers strategic recommendations for the development of better technology-based procurement policies and practices in the future.